Caregiver Perspectives on the Impact of Child Life Specialists during Pediatric Emergency Department Visits - Lundy Day, MD, MEd; Smit Patel, BSc, BN; Manasi Rajagopal, BSc, MBT; Kelly Raymond, MSc, CCLS; Bruce Wright, MD; Sarah Rathwell, MSc; Sandy Stevens, BN; Laura Stevens; Samina Ali, MD (Journal of Pediatrics: Clinical Practice)
Objectives: To describe and compare caregiver perceptions of their emergency department (ED) experiences with and without child life specialist (CLS) involvement in their child's overall care. Study design: A descriptive cross-sectional survey of caregivers of children aged 0-17 years at a tertiary care pediatric ED was completed from March to August 2021. Survey themes included perceived experience and satisfaction and the impact of child life specialists. Results: A total of 179 caregivers completed the survey; mean age was 38.9 years (SD 8.4), and 68.1% (122/179) were mothers. Caregivers of children with CLS involvement (CLS+) ranked their overall experience (P = .021) and satisfaction (P = .009) greater than without CLS involvement (CLS–). More CLS+ caregivers ranked their experience (55.7%, 34/61) and their satisfaction (77.0%, 47/61) as excellent (5/5 Likert scale rating) compared with CLS– caregivers (34.8%, 40/115 and 52.2%, 60/115 respectively). CLS+ families were more likely to be offered nonpharmacologic interventions (eg, iPad, sensory lights, toys) (98.4% vs 31.3%, P = .003); they were also more likely to have a health care worker explore their feelings and fears (52.5% vs 27.0%, P = .0008), help them prepare for a procedure or examination (73.8% vs 31.3%, P < .0001), provide distraction techniques (70.5% vs 19.1%, P < .0001), offer strategies to help coping (47.5% vs 14.8%, P < .0001), or provide play opportunities (55.7% vs 9.6%, P < .0001). Conclusions: CLS involvement in children’s ED care is associated with greater caregiver satisfaction and experience beyond previously reported procedural distress management. Efforts to increase availability of CLSs should be made to better family experiences in the ED.